(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the prevalence and characteristics of occupational stress among nurses at Hung Yen General Hospital in 2024. Methods: A cross-sectional study was conducted among 176 nurses using the Expanded Nursing Stress Scale (ENSS). Results: The mean age of the study subjects was 38.19 ± 4.8; with female accounting for 89.2%; average length of service was 13.8 ± 4.7 years. Most nurses experienced low levels of stress (73.3%), while 26.7% reported moderate stress; no cases of high stress were observed. Among the surveyed areas, stress related to patients and their families had the highest average score (2.0 ± 0.6) and was at a moderate level. Conclusion: Nurses at Hung Yen General Hospital mainly experience low-level stress; stress related to patients and their families is an area that needs priority intervention.